The role of urine β2-MG concentration and the urine MAU/UA ratio in the diagnosis and risk stratification of hypertension-induced renal damage : urine β2-MG concentration and the urine MAU/UA ratio in hypertension-induced renal damage - Huang, Chezhao; Zhuang, Yanshuang; Xue, Peng; Zhang, Hui; Zhao, Yucong; Huang, Zeyu; Tian, Hu; Zhai, Liping; Ma, Teng (Journal of Medical Biochemistry, 2026)
Objective To explore the roles of urineβ2-microglobulin (β2-MG) and the ratio of microalbuminuria (MAU) to uric acid (UA) in the diagnosis of renal damage and risk stratification assessment of the prognosis of essential hypertension with H-type (EH) hypertension. Methods From January to December 2025, 204 patients with H-type EH and renal damage who were admitted to our hospital were selected and included in the renal damage group, whereas 102 patients with H-type EH but without renal damage were included in the EH group. The baseline data of all patients were collected. The urine β2-MG, urinary MAU, and UA levels of all patients were detected, and the MAU/UA ratio was calculated. The β2-MG levels and MAU/UA ratios of the two groups were compared, and multivariate logistic regression analysis was used to explore the factors influencing renal damage in patients with H-type EH. Patients with EH-related renal damage were divided into a low- to moderate-risk group and a high-risk group on the basis of the prognostic risk stratification at admission. A receiver operating characteristic (ROC) curve was drawn to analyze the predictive value of the urine β2-MG concentration and the urine MAU/UA ratio for the prognostic risk stratification of H-type EH renal damage. Results Compared with those in the EH group, the proportion of patients with renal damage combined with diabetes, the urine β2-MG level, and the urine MAU/UA ratio were significantly greater (P<0.05). The results of multivariate logistic regression analysis revealed that elevated urine β2-MG levels and the urine MAU/UA ratio were independent risk factors for renal damage in H-type EH patients (P<0.05). The prognostic risk stratification results revealed that there were 122 patients in the low- to moderate-risk group and 82 patients in the high-risk group; the urine β2-MG level and urine MAU/UA ratio in the high-risk group were significantly greater than those in the low- to moderate-risk group (P<0.05). The ROC curve analysis results revealed that the individual and combined prediction of the urine β2-MG concentration and the urine MAU/UA ratio for high-risk renal damage in H-type EH patients had AUC values of 0.781, 0.786, and 0.860, respectively, and the combined prediction AUC was significantly greater than the individual prediction AUC of the urine β2-MG concentration and the urine MAU/UA ratio (Z = 2.035, 1.953; both P<0.05). Conclusion The urine β2-MG level and urine MAU/UA ratio in patients with H-type EH renal damage are high. Moreover, increases in the urine β2-MG level and the urine MAU/UA ratio are independent risk factors for the occurrence of renal damage in H-type EH patients. The combined detection of these two indicators has high predictive value for the risk stratification assessment of renal damage in H-type EH patients.